Development of a Formalized, Multifaceted Mentorship Program in Physical Medicine and Rehabilitation Residency Education. (February 2022) - Liang, Jason; Kempenaar, Ainsley; Sequeira, Nicholas; Becker, Lisa
Abstract : Abstract: Mentorship in medicine has long been a vital component to the training, development, and career advancement of physicians. Although optimal strategies for facilitating mentorship relationships are unknown, it is recognized that establishing a formalized mentorship program within residency training may augment mentor-mentee pairing, improve overall trainee experience, and enhance resident perception of strong mentoring relationships. A formalized mentorship program was successfully developed in a Canadian physical medicine and rehabilitation residency program, including innovations such as near-peer self-matching, a needs assessment survey, a speed dating event, formation of "link groups, " and "fireside chats" with faculty members. This approach may serve as a guide for other medical education and residency programs seeking to implement a similar concept.